Enhanced protein synthesis is a defining requirement for neonatal B cell development - Åkerstrand, Hugo; Boldrin, Elena; Montano, Giorgia; Vanhee, Stijn; Olsson, Karin; Krausse, Niklas; Vergani, Stefano; Cieśla, Maciej; Bellodi, Cristian; Yuan, Joan (Frontiers in Immunology, 2023)
The LIN28B RNA binding protein exhibits a ontogenically restricted expression pattern and is a key molecular regulator of fetal and neonatal B lymphopoiesis. It enhances the positive selection of CD5+ immature B cells early in life through amplifying the CD19/PI3K/c-MYC pathway and is sufficient to reinitiate self-reactive B-1a cell output when ectopically expressed in the adult. In this study, interactome analysis in primary B cell precursors showed direct binding by LIN28B to numerous ribosomal protein transcripts, consistent with a regulatory role in cellular protein synthesis. Induction of LIN28B expression in the adult setting is sufficient to promote enhanced protein synthesis during the small Pre-B and immature B cell stages, but not during the Pro-B cell stage. This stage dependent effect was dictated by IL-7 mediated signaling, which masked the impact of LIN28B through an overpowering stimulation on the c-MYC / protein synthesis axis in Pro-B cells. Importantly, elevated protein synthesis was a distinguishing feature between neonatal and adult B cell development that was critically supported by endogenous Lin28b expression early in life. Finally, we used a ribosomal hypomorphic mouse model to demonstrate that subdued protein synthesis is specifically detrimental for neonatal B lymphopoiesis and the output of B-1a cells, without affecting B cell development in the adult. Taken together, we identify elevated protein synthesis as a defining requirement for early-life B cell development that critically depends on Lin28b. Our findings offer new mechanistic insights into the layered formation of the complex adult B cell repertoire.